Magnetization and ferromagnetic resonance in a Fe/Gd multilayer: experiment and modelling. (3rd February 2017) - Drovosekov, A B; Kreines, N M; Savitsky, A O; Kravtsov, E A; Ryabukhina, M V; Proglyado, V V; Ustinov, V V
Abstract: Static and dynamic magnetic properties of a [Fe(35 Å)/Gd(50 Å)]12 superlattice are investigated experimentally in the temperature range 5–295 K using SQUID magnetometery and the ferromagnetic resonance (FMR) technique at frequencies 7–38 GHz. The obtained magnetization curves and FMR spectra are analysed theoretically using numerical simulation on the basis of the effective field model. At every given temperature, both static and resonance experimental data can be approximated well within the proposed model. However, a considerable temperature dependence of the effective field parameter in gadolinium layers has to be taken into account to achieve reasonable agreement with the experimental data in the entire temperature range studied. To describe the peculiarities of experimental FMR spectra, a non-local diffusion-type absorption term in Landau–Lifshitz equations is considered in addition to the Gilbert damping term. Possible reasons for the observed effects are discussed.